Know Thy Kit—Why Catheter Design Matters! - Heinrich, Henriette (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Heinrich H. Know thy kit – why catheter design matters! Turk J Gastroenterol. 2025;36(8):477-478.